The Status of Alternative Assessment in Morocco: Teachers’ Attitudes and Obstacles - kasmi, hicham; Anasse, Khadija (International Journal of Language and Literary Studies, 2023)
Assessment is a fundamental part in language teaching/learning process. It is a guiding factor that provides insight to teachers and learners about the best way to proceed. The literature about language assessment is rich. It includes different forms and techniques of language assessment. In this paper, however, the focus is mainly on alternative assessment. The latter is different both in form and nature from traditional assessment. Researchers confirm that if applied properly, alternative assessment can reflect students’ progress and motivate them to keep up the hard work. This paper, hence, aims to study the attitude of language teachers toward alternative assessment and the main obstacles that may hinder its application in the Moroccan classroom. This research is quantitative. It uses a questionnaire as the main data collection tool. The findings indicate that teachers hold a positive attitude toward alternative assessment, but they fail to apply it in their classroom due to different obstacles.